Needs Analysis Of Malay Literacy Teaching Management Module Development: Perception Of Teachers - Kamal, Nurfara Syakila; A. Ghani, Muhammad Faizal (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2025)
Needs analysis is conducted in module development research to ensure that the products produced can meet the needs of users. Failure to master reading skills early in schooling will lead to failure to master other skills, resulting in the student dropping out of continuing to develop their potential. As a result, this study was conducted to determine the need for literacy module development. This study's specific goal is to identify the need for malay literacy teaching management modules based on teachers' perceptions. This study uses a case study design with a qualitative method approach to gather information and data from four teachers who served as the study sample through semi-structured interviews. Thematic analysis was used to extract themes and sub-themes from the data in order to answer the research questions. The data analysis findings revealed six main themes: (1) Learning Content, (2) Classroom Management, (3) Students' Learning Ability, (4) Module Criteria, (5) Teaching Strategies, and (6) Assessment Needs, indicating the need to develop literacy modules. Aside from the six main themes identified, the recommendations and specifications obtained through interviews with informants provide useful input to researchers for use in designing and developing modules in the next phase, as well as assisting researchers in producing systematic literacy modules.